Atitudes negativas frente a vítimas de estupro: considerações acerca da atribuição de causa e culpa - Silva, Francicléia Lopes (2020)
This dissertation aimed to verify which aspects minimize the aggressor's perception of guilt in rape, admitting the orientation to social dominance and human values as predictors. In this sense, two articles were made. Article 1 aimed to gather psychometric evidence of the adaptation of the Rape Cause Perception Scale. This article was divided into two studies, the first counting the participation of 220 university students from the city of João Pessoa - PB, of both sexes (64.5% female), with an average age of 23.48 years (SD = 7, 56; range from 18 to 63 years). These answered, in addition to sociodemographic questions, the Brazilian version of the measure of perception of the cause of rape, in the second study, the sample consisted of 203 university students of both sexes (54.2% female), with an average age of 21 , 45 years old (SD = 5.17; range from 18 to 51 years old), who answered the Brazilian version of the instrument and the measure of Attitudes towards Rape Victims (EAVE). The analyzes corroborated the factorial structure of 5 components as suggested by the original version of the instrument, these components are organized in individual order styles: Blaming the Victim (α = 0.86), Male Sexuality (α = 0.84) and Male Hostility (α = 0.70); and social styles: Male Domination (α = 0.92) and Society / Socialization (α = 0.86). Finally, the confirmatory analysis of the second study corroborates the instrument's pentafactorial structure (eg, χ2 / gl = 2.00, GFI = 0.81, AGFI = 0.78, CFI = 0.88, RMSEA = 0.07 (CI90% = 0.062-0.078), ECVI = 3.47 and CAIC = 969.427) and its convergent validity with the EAVE scale. Article 2 is a study of a quasi-experimental character, 2x2 and aimed to analyze the influence of normative human values and the orientation to social dominance in the perception of the cause of rape in negative attitudes towards victims. 369 university students from a public institution in João Pessoa - PB participated in this study. These had a mean age of 21, 32 years (SD = 4.53; range of 18 to 49 years), the majority being male (52.9%), who answered sociodemographic questions and the measures: Scale of Perception of Rape Cause (EPCE), Attitude Scale Against Rape Victims (EAVE), Basic Values Questionnaire (QVB), SDO Social Dominance Orientation Scale, and in addition to the aforementioned instruments, an experimental scenario was used where the the victim's ethnicity and the context in which the victim took the situation that the violence occurred. The results corroborate those found in the existing literature, men continue to be those who show greater negative attitudes towards victims of rape; people who identify with the feminist movement tend to endorse less support for negative attitudes towards victims of rape, it can also be seen that black victims are more to blame for the violence they suffer; being able to verify that the orientation to social dominance as well as the normative values are predictors of the attitudes towards victims of rape, being the perception of cause of social rape a mediator in the reduction of blame for the rape victim (eg, coefficient = 0, 0294, SE = 0.0091, CI90% = 0.0130 to 0.0492). Thus, it is estimated that the proposed objectives have been achieved.